Effort to engage Magnification Devices in Educational Tonsillectomy - A prospective clinical trial - K Stelter; SH Kim; L Geerke; U Kisser; C Reichel; S Vögele; F Schrötzlmair (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Introduction: Most educational hospitals teach the tonsil surgery just with head lights and without any magnification device. This prospective clinical trial focuses on the additional workload when using a microscope or magnifying glasses for tonsillectomy.  Material and methods: four surgeons in training with no experience in tonsil surgery operated on 48 patients who underwent elective extra capsular tonsillectomy. Surgery was either performed on one patient´s side with the naked eyes plus headlamp and on the other side with magnifying glasses or a microscope. The surgeons were connected to a biofeedback device in order to monitor the breathing frequency, the heart rate variability and the masseter tone. After every operation surgeons filled out the NasaTLX questionnaire for evaluating the cognitive workload during surgery.  Results: There was a significant difference in the questioning and the heartrate variability when using the microscope compared to the naked eyes and the magnifying glasses. However, there was no statistical difference in mean operation time for all study arms.  Conclusion: Compared to loupes the mental distress is higher when operating a microscope in the first eight times. Despite the many advantages of an OR-microscope, this fact may hinder the usability of such a device in tonsillectomy